Dipeptidyl Peptidase-4 Inhibitors Use and Relative Risk of Ischemic Cerebrovascular Disease in Type 2 Diabetic Patients in a Case-Control Study - Lai, Shih-Wei; Liao, Kuan-Fu; Lin, Cheng-Li; Lin, Hsien-Feng (Frontiers in Pharmacology, 2017)
Background and Objectives. Limited research focuses on the risk of ischemic cerebrovascular disease associated with use of dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors) in patients with type 2 diabetes mellitus in Taiwan. This study aimed to investigate the association between DPP-4 inhibitors use and the first episode of ischemic cerebrovascular disease. Methods. We designed a case-control study using the database of the Taiwan National Health Insurance Program. There were 1999 type 2 diabetic subjects aged 20-84 years with the first episode of ischemic cerebrovascular disease from 2000 to 2013 as the cases, and 7996 sex- and age-matched, randomly selected type 2 diabetic subjects aged 20-84 years without any type of cerebrovascular diseases as the matched controls. We estimated the odds ratio (OR) and 95% confidence interval (CI) of ischemic cerebrovascular disease associated with cumulative duration of DPP-4 inhibitors use by the multivariable logistic regression model. Results. After adjustment for confounding variables, the adjusted OR of ischemic cerebrovascular disease was 0.96 (95% CI 0.95, 0.97) in subjects with ever use of DPP-4 inhibitors as increase in use duration for every one month, compared with never use. The sub-analysis disclosed that the adjusted ORs of ischemic cerebrovascular disease were 1.57 (95% CI 1.36, 1.80) for subjects with cumulative duration of DPP-4 inhibitors use < 1 year, and 0.70 (95% CI 0.57, 0.87) for subjects with cumulative duration of DPP-4 inhibitors use ≥ 1 year, compared with never use. Conclusions. Our findings suggest that DPP-4 inhibitors use correlates with relative risk reduction of the first episode of ischemic cerebrovascular disease in type 2 diabetic patients in a duration-dependent response. The beneficial effect will be marked when DPP-4 inhibitors use is ≥ 1 year.